On Economic Interdependence and War - Morelli, Massimo; Sonno, Tommaso (Journal of Economic Literature, 2017)
In this article, we review the book Economic Interdependence and War by Dale C. Copeland, and take this opportunity to describe and discuss the current debate on the topic from an interdisciplinary perspective. We also provide novel insights on the measurability of dependence expectations' effects on conflict, using the interaction with geography and endowment asymmetries. (JEL D74, D84, F14, F51, Q34)